Old-Indian Váruṇa in the Light Of Balto-Slavic Mythological “Fish-King” or “Fish-Herdsman” - Разаускас Дaйнюc (Acta Orientalia Vilnensia, 2004)
There is a figure in the Balto-Slavic folk tradition of the so-called “Fish-King” who at the same time is a “Fish-Herdsman”, or “Herdsman of Fishes”, whose herds consist of fishes conceived as swines, cows, horses, etc. Sometimes he also appears in the shape of fish, usually “large fish”. The motif in reconstruction derives from the mixture of well-known ideas of the Underworld as a pasture of souls and the Underworld in the waters with the deceased souls as fishes; cf., for instance, the Irish Manannán mac Lir with his undersea pastures whose herds appear to Bran from above as flocks of fishes and whose Otherworld merged afterwards with the Christian Paradise. Furthermore, the Christian Saviour Himself is the Fish (cf. at least the Greek word for fish ichthýs conceived as the acronym for Iēsū̃s Christòs The ū Yiòs Sōtḗr “Jesus Christ, Son of God, Saviour”, etc.) and the Fisherman of Men (Matthew 4:18-19, etc.), and at the same time He is the Shepherd (John 10:1-16, etc.). So the notion of “Herdsman of Soul-Fishes” must be regarded as archaic and widespread indeed. The Vedic Váruṇa-, in his turn, is not only called síndhupali “Lord of the sea, or the rivers” (RV VII.64.2) and moves in the sea (RV 1.161.14) but is also, especially in later sources, closely connected with fishes (cf. váruṇa “related to Váruṇa” and “fish”), and sometimes even identified with fish. On the other hand, he is the Lord of the Dead (RV X.14.7) and at the same time the Herdsman (gopā́ḥ: RV VIII.41.1), “the Herdsman of the World” in common with Mitra (bhuvanasya gopā: RV Y.62.9), and finally “the Herdsman of Immortality” (am.nasya gopā́ḥ: RV VIll.42.2), almost the “Saviour”, so to say. Furthermore, he is once said to move at the same time in “the Waters” and in “all Creatures” (RV X.177.3), which is very close to the image of the Herdsman of Soul-Fishes as we see it, for instance, in the Balto-Slavic tradition.